Anatomy of seismograms: developments in Soild earth geophysics - Kulhanek, Ota (New York Elsevier, 2020)
An interactive multimedia anatomical dissection and medical information organizing package, at a level consistent with an intermediate level human anatomy course. Contains accurate cut-away illustrations in four views (anterior, posterior, medial and lateral) of the complete anatomy of the human body. Features include gender and race options, simulated disection, image rotation and magnification, multiple views of layered structures, cross sections, histologies, radiologies, animations of simulated injuries and surgeries, and software that enables the creation of custom and interactive documents and presentations.
Keywords: Human anatomy; Human dissection